2011
DOI: 10.1007/s10995-011-0846-1
|View full text |Cite
|
Sign up to set email alerts
|

Trimester of Maternal Gestational Weight Gain and Offspring Body Weight at Birth and Age Five

Abstract: To investigate associations of trimester-specific GWG with fetal birth size and BMI at age 5 years. We examined 3,015 singleton births to women without pregnancy complications from the Child Health and Development Studies prospective cohort with measured weights during pregnancy. We used multivariable regression to examine the associations between total and trimester gestational weight gain (GWG) and birth weight for gestational age and child BMI outcomes, adjusting for maternal age, race/ethnicity, education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 28 publications
10
108
1
1
Order By: Relevance
“…In previous studies, investigators (8,30,31) found that absolute, week-specific GWG in the first and second trimesters was more relevant for the risk of later overweight in the offspring than week-specific GWG in the third trimester. These findings would suggest that most of the association of GWG on overweight in the offspring is determined in the first two trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, investigators (8,30,31) found that absolute, week-specific GWG in the first and second trimesters was more relevant for the risk of later overweight in the offspring than week-specific GWG in the third trimester. These findings would suggest that most of the association of GWG on overweight in the offspring is determined in the first two trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…A limita on of the study was that it did not control for certain poten al confounders: gesta onal diabetes mellitus, gene c characteris cs, nausea, diet, or physical ac vity. In addi on, unlike the Fraser et al, Margerison-Zilko found there to be eff ect modifi ca on by pre-pregnancy BMI 7 .…”
Section: Trimester Of Gestational Weight Gainmentioning
confidence: 75%
“…Only three studies were found in the literature search to have examined whether trimester-specifi c GWG associates with off spring adiposity later in life as their primary or secondary objec ves, two of them being European cohort studies 7,22,23 . Fraser et al examined the importance of IOM guidelines and off spring adiposity directly with Avon Longitudinal Study of Parents and Children (ALSPAC) prospec ve pregnancy cohort in UK 22 .…”
Section: Trimester Of Gestational Weight Gainmentioning
confidence: 99%
See 2 more Smart Citations